2020
DOI: 10.1177/2192568220948830
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Axial Vertebral Rotation in Adolescent Idiopathic Scoliosis: Is the Apical Vertebra the Most Rotated?

Abstract: Study Design: Retrospective cross-sectional study. Objectives: It is generally believed that the apical vertebra has the largest axial rotation in adolescent idiopathic scoliosis. We investigated the relationship between apical axial vertebral rotation (apicalAVR) and maximal axial vertebral rotation (maxAVR) in both major and minor curves using biplanar stereo-imaging. Methods: EOS 2D/3D biplanar radiograph images were collected from 332 patients with adolescent idiopathic scoliosis (Cobb angle range 10°-122°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…Knowledge of the reliability and reproducibility of a measure makes it possible to determine whether the effect of an intervention is greater than the variability of the measure itself and, therefore, whether it is real. 14,17 Marawar et al, 13 in an experimental study using synthetic models of vertebrae, found low agreement of the Nash & Moe classification (38.2% -53.9%) compared to the Upasani method (76.74% -80.23%). Kuklo et al, 7 using digital measurements, found only fair interobserver reliability (r= 0.53-0.59).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Knowledge of the reliability and reproducibility of a measure makes it possible to determine whether the effect of an intervention is greater than the variability of the measure itself and, therefore, whether it is real. 14,17 Marawar et al, 13 in an experimental study using synthetic models of vertebrae, found low agreement of the Nash & Moe classification (38.2% -53.9%) compared to the Upasani method (76.74% -80.23%). Kuklo et al, 7 using digital measurements, found only fair interobserver reliability (r= 0.53-0.59).…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of the axial plane of AIS, with rotation of the apical vertebra as its most important parameter, has attracted increasing interest in recent years. 1,2,[5][6][7]9,13 The degree of vertebral rotation can be useful for monitoring the progression of scoliosis and assessing treatment results. 5,[14][15][16] Accurate assessment of vertebral rotation allows prediction of curve progression, the degree of correction, and possible decompensation of the coronal balance of the spine in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The EOS imaging system is a cutting-edge, low-radiation, and highly accurate method for assessing spinal curvature. Some studies [28][29][30][31] have used EOS images to create comprehensive 3D spine reconstructions, forming the basis for measuring vertebral rotation angles with specialized software. While EOS imaging has been used to reconstruct 3D vertebral models in certain studies, measuring vertebral rotation angles often involves time-consuming manual point marking.…”
Section: Eos Imaging Systemmentioning
confidence: 99%
“…I.-L. V. csigolyákra. Az axiális csigolyarotációk adatsorából meghatároztuk az apicalAVR és a maximális csigolyarotáció (maxAVR) értékeit [24].…”
Section: Eos 2d/3d Képalkotásunclassified
“…Az elterjedtebb apicalAVR-alapú vizsgálattal 56,7%-os derotációs hatékonyságot értünk el, amely érdemben megegyezik a szakirodalmi adatokkal [27]. A scoliosis axiális dimenzióját teljeskörűbben leíró maxAVR szerinti módszerrel 55,2%-os derotációs sikerességet mértünk [24]. A két módszer százalékos végeredményében azért nem érzékelhető érdemi különbség, mert a maxAVR az apical-AVR-nél szignifikánsan magasabb volt a preoperatív és a posztoperatív esetekben is, kiegyenlítve a kettőből számított műtéti hatékonyság mértékét.…”
Section: Megbeszélésunclassified